Defense Strategies in Safeguarding Maritime Security in Indonesia's Outermost Small Islands - Dao, Yunias; Yusnaldi; Kusuma (Indonesian Scientific Publication, 2024)
The outermost small islands of Indonesia play a critical role in maintaining national sovereignty and maritime security. However, these areas face significant challenges, including resource limitations, non-traditional threats, environmental vulnerabilities, and weak inter-agency coordination, which impede the effectiveness of current defense strategies. This study investigates how Indonesia's defense strategies address maritime security challenges and proposes actionable solutions to enhance their effectiveness. While previous research has broadly examined maritime security, few studies focus specifically on the strategic intricacies of the outermost small islands, highlighting the novelty of this paper. A qualitative research approach is employed, utilizing a systematic literature review to analyze data from scientific journal articles, policy reports, and government documents. The thematic analysis identifies key challenges, current strategies, and opportunities for improvement. The findings reveal that existing strategies—such as strengthening maritime policies, enhancing the capacity of the Indonesian Navy and the Maritime Security Agency (Bakamla), and engaging in maritime diplomacy—are hampered by budgetary constraints, weak inter-agency coordination, and insufficient technological integration. The study recommends enhancing maritime infrastructure, adopting advanced surveillance technologies, empowering local communities, and fostering international collaboration to address transnational threats. This study concludes that an integrated and evidence-based defense strategy is essential to safeguard Indonesia’s maritime borders. The findings underscore the need for policy reforms that adopt a multidimensional approach, reinforcing Indonesia's position as a resilient and sovereign maritime nation.